Basics of medical physiology - Ostatníková, Daniela, 1957- (Comenius University in Bratislava, 2021)
The textbook was prepared to provide students studying General Medicine and Dentistry with grounding in particular chapters of human physiology while encouraging further and more detailed preclinical and clinical studies. The content is centred on the main mechanisms of all organ systems and their regulations. The new opening chapter on physiological regulations was included to point out the importance of complex cell-organ-system regulatory functions of the human body. Following chapters include general neurophysiology as the base for the overall body functioning and sensory physiology that outlines the information inputs for the brain processing, followed by the central nervous system. This defines functions of the central sensory and motor systems and provides the basic understanding of the higher nervous functions unique to human beings. The following chapters deal with basic information on fundamental functions of the body systems with explanation of the basic structures and functional mechanisms, outlying the principles of their regulations referring to the blood, the heart and blood vessels, the lungs and kidneys, the digestive system and nutrition and metabolism. Separate chapters are devoted to endocrinology and reproduction functions overview. The final chapter on neuro-endocrine-immune interactions will add to understanding of the complex regulation of human body during the life span in relation to its homeostasis and health preservation.